International taxation of multinational enterprises (MNEs) - Fernandez, Prafula; Pope, Jeffrey (Bond University - Commercial Law Centre, Faculty of Law, 2003)
MNEs are likely to continue to grow because of factors such as globalisation and electronic commerce. Many countries are reforming their international tax systems in order to attract MNEs into their jurisdictions to do business within their borders and also to promote overseas growth of their resident corporations. Issues such as taxation of electronic commerce, transfer pricing and harmful tax competition need to be addressed. Practical solutions for the future can include: a model convention for the taxation of MNEs; unitary accounting for MNEs; a multilateral treaty; or a global system of registration of MNEs.